Development of alphabet maze media for beginning reading skills for children - Nafiah, Intan Nur; Wijayanti, Arwendis; Sukmono, Nur Dwi (Universitas Islam Negeri Raden Intan Lampung, 2022)
Reading ability affects children's success in understanding learning material. Teachers who are less creative in carrying out reading activities and the lack of use of learning media have an impact on children so that children have difficulty saying words with good and fluent intonation. This study aims to produce effective, efficient, and interesting alphabet maze media for reading skills. In this research and development, the researcher uses the ADDIE development model. This model uses a five-step development procedure: analysis, design, development, implementation, and evaluation. The data collection instruments used in this research and development are questionnaires and observations. The data analysis technique used in the research and development of the alphabet maze media is in the form of quantitative data and qualitative data. The results shown from the analysis of product development of alphabet maze media have the achievement of eligibility or validity in the form of very valid, in terms of effectiveness very effective, aspects of efficiency are very efficient, attractiveness aspect is very interesting. Based on these percentages, the researchers can conclude that alphabet maze media for early reading skills is said to be very valid in terms of aspects of effectiveness, aspects of efficiency, and aspects of attractiveness. Applying this media also makes it easier for teachers to adjust teaching to children. In addition, the success of using the alphabet maze media was shown in the attitude of the children, who were enthusiastic and more enthusiastic about learning to read at the beginning.